Pro-Resolving Factor Administration Limits Cancer Progression by Enhancing Immune Response Against Cancer Cells - Wetzel, Audrey; Bonnefoy, Francis; Chagué, Cécile; Vetter, Mathieu; Couturier, Mélanie; Baffert, Blandine; Adotévi, Olivier; Saas, Philippe; Perruche, Sylvain (Frontiers in Immunology, 2022)
Cancers are consequences of cellular dysfunction leading to an aberrant cellular multiplication and proliferation, subsequently yielding metastasis formation. Inflammatory reaction, with immune cell recruitment, is the main defense against precancerous lesions. However, an inflammatory environment also favors cancer cells progression, with cancer cell evasion from immune surveillance, leading to cancer development. Current therapeutic strategies enhance this natural immune response in order to restore immunosurveillance. The variety of these strategies is a predominant source of inflammatory mediators used by cancer cells to grow, differentiate and migrate, therefore encouraging metastasis formation. For this reason, during cancer progression, limiting inflammation appears to be an innovative strategy to avoid the escape of cancer cells and potentially enhance the efficacy of anti-tumor therapies. Thus, this study aims to investigate the impact of administering pro-resolving factors (SuperMApo® drug candidate), which are inducers of inflammation resolution, in the framework of cancer treatment. We have observed that administering pro-resolving mediators issued from apoptotic cell efferocytosis by macrophages controlled peritoneal cancer progression by limiting cancer cell dissemination to the blood and mesenteric lymph nodes. This observation has been linked to an increase of macrophage mobilization in both peritoneal cavity and mesenteric lymph nodes. This control is associated to a restricted immunosuppressive myeloid cell circulation and to an IFN-γ specific anti-tumor T cell response. Altogether, these results suggest that administering pro-resolving factors could provide a new additional therapeutic alternative to control cancer progression.